Promoting plant-based eating in meat-centric meal contexts: a field study - David Guedes; Vasco Brazão; Lisa Roque; Lúcia Campos; Cristina Godinho; Monica Truninger; Markus Vinnari; João Graça (Cambridge University Press, 2023)
Abstract Objective: Shifting from meat-centric to plant-rich diets may help to enable healthier and more sustainable food systems. Here we present the results of a 1-week intervention to promote plant-based eating in a meat-centric food context (i.e. canteen). Design: The intervention included environmental restructuring strategies (e.g. promotional materials and menu redevelopment) and improvements to the offer of plant-based meals. The evaluation (sales data; pre-registered) spanned 3 weeks prior to the intervention (baseline), 1 week during the intervention (immediate/short-term impact) and 3 weeks after the intervention (follow-up). Opinion surveys were also used to collect data with customers during the intervention. Setting: Canteen unit of a university campus in Portugal (Lisbon metropolitan area). Participants: In addition to sales data (baseline: 7965 meals; immediate/short-term: 2635 meals; follow-up: 7135 meals), we used opinion surveys to assess customers' meal appraisals during the intervention (n = 370). Results: The odds of a sold meal being vegetarian were 24 % higher in the intervention week compared with the pre-intervention period [OR = 1·24, 95 % CI (1·10, 1·40)] and 9 % higher in the post-intervention period compared with the pre-intervention period [OR = 1·09, (95 % CI (1·00, 1·19)]. Survey data showed that vegetarian meals compared favourably to meat and fish alternatives in liking, sustainability and satiety. Conclusions: A short-term, theory-driven, operationally feasible intervention was effective in promoting increased plant-based meal choices in a collective meal context. Nevertheless, these changes were not entirely sustained over time. Future studies could test whether prolonged or more transformative interventions are necessary to unlock entrenched food practices more effectively in meat-centric collective meal contexts.